Treatment of pediatric myelodysplastic syndromes and juvenile myelomonocytic leukemia: the Brazilian experience in the past decade - Valera, E. T.; Latorre, MDD; Mendes, W. L.; Seber, A.; Lee, MLM; de Paula, MJA; Loggetto, SR; Velloso, E.; Niero-Melo, L.; Lopes, L. F. (Elsevier B.V., 2004)
Background: Therapy strategies for myelodysplastic syndromes (MDS) and juvenile myelomonocytic leukemia (JMML) vary considerably. Objective: To review the treatment of Brazilian children who were diagnosed with MDS or JMML in the past decade and reported to the Brazilian Cooperative Group on Pediatric Myelodysplastic syndromes (BCG-MDS-PED). Results: of 173 children reported to the BCG-MDS-PED from January 1997 to January 2003 with a suspected diagnosis of MDS or JMML, 91 had the diagnosis confirmed after central review of the bone marrow aspirate and biopsy. Information on previous treatments was available for 78 MDS/JMML patients. Treatment varied from different schedules of low-dose (14%) and standard-dose chemotherapy (50%), granulocyte-colony-stimulating factor (G-CSF 7%), interferon (5%), steroids (2%) and erythropoietin (2%) to allogeneic stem-cell transplantation (SCT) (14%). No survival advantage could be demonstrated based on Hasle's classification or based on treatment. Conclusion: This report reflects the current practice in treating Brazilian children with MDS/JMML without specific Cooperative Group guidelines. Treatment modalities were very heterogeneous. The strategies for implementing a national protocol should consider international guidelines and focus on local experience and available resources. (C) 2004 Elsevier Ltd. All rights reserved.
Keywords: myelodysplastic syndromes; children; treatment; neoplasm